PHARMACEUTICAL WASTEWATER TREATMENT: A PHYSICOCHEMICAL STUDY - Saleem, Muhammad (Journal of Research (Science), 2025)
A physicochemical study for the treatment of pharmaceutical wastewater was performed. Objective of the laboratory investigation was to study the removal of color, Total Dissolved Solids (TDS), Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), turbidity and phenol and bring them up to the allowable limits for reuse purposes. Efficiency of coagulation, flocculation, sedimentation, sand filtration followed by activated carbon adsorption was determined. It was found that tested coagulants (alum, ferric chloride, and ferrous sulphate) are not much effective and required high dosage for the removal; of TSS, BOD, COD and turbidity. Alum was found to be more effective among tested coagulants and reduce TSS, BOD, COD and turbidity 79.6%, 34.8, 48.6% and 69.2% respectively. Sand filtration further reduced the studied parameters 97.7%, 95.7%, 93.9% and 76.9% respectively. As the concentration of phenol in the studied pharmaceutical wastewater was 100 mg/l, granular activated carbon was used to remove phenol up to the allowable limit for reuse purpose. Activated carbon adsorption further reduces phenol, TDS, TSS, BOD, and COD up to 99.9%, 99.1%, 21.4%, 81.3% and 71.1% respectively. High removal of color observed after activated carbon adsorption. It was concluded that the suggested treatment scheme is suitable to bring the effluent quality up to the water quality standards.